Revision of the cichlid fish genus Gnathochromis (Teleostei: Cichlidae) from Lake Tanganyika with the description of a new genus Jabarichromis gen. nov. - Haefeli, Anja; Schedel, Frederic D.b.; Ronco, Fabrizia; Indermaur, Adrian; Salzburger, Walter (Zootaxa, 2024)
The cichlid species flock from Lake Tanganyika is a well-studied system for evolutionary biology research because its species assemblage shows a high degree of endemism and is a product of adaptive radiation. While our understanding of the evolutionary history of Lake Tanganyika cichlids has advanced tremendously over the past decades, their taxonomy received considerably less attention, despite numerous taxonomic misplacements (e.g., polyphyletic genera and species) that have been revealed by phylogenetic studies. One prominent example of a polyphyletic genus is Gnathochromis, which includes two distantly related species, belonging to two different tribes. To resolve this issue, here we present a taxonomic revision based on an extensive morphological dataset obtained from a comprehensive taxon sampling including 587 specimens from 63 taxa. We introduce a new monotypic genus, Jabarichromis gen. nov. for ‘Gnathochromis’ pfefferi, a member of the tribe Tropheini, thereby separating it from the type species of Gnathochromis, G. permaxillaris. As a result, the genus Gnathochromis, which belongs to the tribe Limnochromini, is rendered monophyletic. Further, we provide an additional character to distinguish the recently described genus Shuja, which also belongs to the Tropheini, from its former mostly riverine congeners.